Role of vanadium and pyridine in heteropolycompounds for selective oxidation of alcohols with hydrogen peroxide - Palermo, Valeria (2013)
This study describes the application of heteropolyacids H₃PMo₁₂O₄₀, H₄SiMo₁₂O₄₀, H₄PMo₁₁VO₄₀, H₅PMo₁₀V₂O₄₀, H₉PMo₆V₆O₄₀, and a hybrid pyridine-modified heteropolyacid with Keggin structure for selective oxidation of alcohols to ketones or aldehydes using aqueous hydrogen peroxide and acetonitrile as solvent. Performance of these different catalysts in 1-phenylethanol oxidation was studied. Influence of reaction temperature, amount of catalyst and hydrogen peroxide and reaction time on the yield of acetophenone was investigated to obtain optimal reaction conditions. Oxidation ability of the catalyst depended on the number of vanadium atoms present in the Keggin ion and to a lesser extent on pyridine substitution in the Keggin secondary structure. In order to explore the applicability of the method for selective oxidation of alcohols to ketones or aldehydes, various alcohols were investigated according to the general procedure using hybrid pyridine-modified heteropolyacid.